Marketing capability, technical capability or degree of product innovation: what really matters in leveraging the sales of technology-based start-ups?. (15th May 2019) - Padrão, Luis Carlos; Andreassi, Tales; Brito, Luiz Artur Ledur
The objective of this study was to analyse the influence of incubator marketing support on the product performance of incubated NTBFs. The study's theoretical contribution sheds new light on NPD in incubated NTBFs by analysing the effect of an important type of incubator support on NPD: incubator marketing support. A total of 512 target NTBFs were identified and 250 participated in the survey. We found that incubator marketing support positively influences marketing capability. Marketing capability is a key factor for promoting sales growth in both low and high turbulence environments, although the effect is more pronounced in low turbulence environments.